Mixture effects of 30 environmental contaminants on incident metabolic syndrome—A prospective study - Lind, Lars; Salihovic, Samira; Lampa, Erik; Lind, P. Monica (Environment international, 2017)
Several cross-sectional studies have linked different environmental contaminants to the metabolic syndrome (MetS). However, mixture effects have not been investigated and no prospective studies exist regarding environmental contaminants and the MetS. To study mixture effects of contaminants on the risk of incident MetS in a prospective fashion. Our sample consisted of 452 subjects from the Prospective Study of the Vasculature in Uppsala Seniors (PIVUS) study (50% women, all aged 70years) free from the MetS at baseline, being followed for 10years. At baseline, 30 different environmental contaminants were measured; 6 polychlorinated biphenyls (PCBs), 3 organochlorine (OC) pesticides, one dioxin, one polybrominated diphenyl ether (all in plasma), 8 perfluoroalkyl substances (in plasma) and 11 metals (in whole blood). The MetS was defined by the ATPIII/NCEP criteria. Gradient boosted Classification and Regression Trees (CARTs) was used to evaluate potential synergistic and additive mixture effects on incident MetS. During 10-year follow-up, 92 incident cases of the MetS occurred. PCB126, PCB170, hexachlorobenzene (HCB) and PCB118 levels were all associated with incident MetS in an additive fashion (OR 1.73 for a change from 10th to 90th percentile (95%CI 1.24–3.04) for PCB126, OR 0.63 (0.42–0.78) for PCB170, OR 1.44 (1.09–2.20) for HCB and OR 1.46 (1.13–2.43) for PCB118). No synergistic effects were found. A mixture of environmental contaminants, with PCB126, PCB170, HCB and PCB118 being the most important, showed associations with future development of the MetS in an additive fashion in this prospective study. Thus, mixture effects of environmental contaminants could contribute to the development of cardio-metabolic derangements. •Mixture effects on health outcomes have not previously been presented in humans.•Mixture effect of 30 contaminants on incident metabolic syndrome was studied.•A mixture of PCB126, PCB170, hexachlorobenzene and PCB118 was identified.•This mixture was related to future metabolic syndrome.•Mixture effects could be evaluated regarding human health.